2017
DOI: 10.1287/mnsc.2015.2293
|View full text |Cite
|
Sign up to set email alerts
|

Old Age and the Decline in Financial Literacy

Abstract: Households age 60 and older bear increasing responsibility for managing retirement portfolios, and they hold the majority of financial assets in the United States. Cognitive aging studies find evidence of a decline in fluid and crystallized intelligence in old age that may impact the ability to manage money effectively. Using a large sample of older respondents, we test whether knowledge of basic concepts essential to effective financial choice declines after age 60. We find a consistent linear decline in fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(108 citation statements)
references
References 33 publications
5
99
0
4
Order By: Relevance
“…As consumers age, their actual financial capability should increase alongside their more complicated financial lives, resulting in an increase in their perceived financial self-efficacy or confidence. Previous research has showed that consumer financial confidence did not decline among consumers aged 60-85 years old (Finke et al, 2011). We then propose the following hypothesis:…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 78%
See 1 more Smart Citation
“…As consumers age, their actual financial capability should increase alongside their more complicated financial lives, resulting in an increase in their perceived financial self-efficacy or confidence. Previous research has showed that consumer financial confidence did not decline among consumers aged 60-85 years old (Finke et al, 2011). We then propose the following hypothesis:…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 78%
“…No previous research was found to focus on subjective financial literacy among older consumers. However, a study focusing on older consumers found that, among consumers older than 60 years, objective financial literacy may decline but financial confidence never does (Finke et al, 2011). If confidence increases with age, then we assume that subjective financial literacy should also increase with age.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 96%
“…The relationship between age and financial self-efficacy is less clear. Some have raised concern about a financial knowledge gap, where older adults overestimate their financial knowledge in greater frequency than younger adults (Finke, Howe, and Huston 2016;Khan et al 2017).…”
Section: Age and Financesmentioning
confidence: 99%
“…A literatura documenta evidências de que os norteamericanos estavam menos convictos de que possuíam fundos suficientes em suas aposentadorias para manter seus respectivos padrões de vida (The Hartford, 2009). (Finke, Howe, & Huston, 2017;Fisher, 2010;O'Neill & Xiao, 2012). A Tabela 1 apresenta as variáveis independentes e dependentes.…”
Section: Estrutura Teórica E Literatura Relacionadaunclassified